APN : the monthly magazine for gay people. (Leeds : All Points North Publications, 1993)
Fonds Suzan Daniel (FSD)
Periodiciteit: maandelijks
Redactie: Walk 34, Middleton Road, Morley, Leeds LS27 8BB
Engels
Periodiek